“ULAR TANGGA OLAHRAGA” MEDIA PERMAINAN EDUKATIF UNTUK OLAHRAGA DENGAN MENGGUNAKAN SISTEM SIRKUIT TRAINING BAGI SISWA KELAS X SMA NEGERI AJIBARANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
The goal is to develop and produce products such as Snakes and Ladders game model which refers to the sports-based student-centered learning.The analysis procedure includes product development product that will be created, developed the initial product, expert validation and revision, testing and revision of a small group, large group and test the final product. The data was collected using a questionnaire derived from the evaluation of experts and students. The data analysis technique used is descriptive percentages.From the test results obtained by the expert evaluation data, expert penjas 84% (good), learning experts I 88% (good), a learning II 82.6% (good), a small test group 89% (good), and the test field 92% (very good). From the available data it can be concluded that the learning model sport through Sport Snakes and Ladders game can be used for high school students of State Ajibarang Banyumas.Based on the above results, Sport Snakes and Ladders game effectively applied in sports.